Transient Complete Asthenozoospermia - Artenisa Kulla; Basil Mirza; Kevin James Campbell (Wolters Kluwer Medknow Publications, 2024)
Limited research exists on the mechanisms underlying asthenozoospermia associated with acquired ciliary dyskinesia. Primary ciliary dyskinesia links respiratory pathology with infertility and provides a basis for a potential mechanism. The aetiology of asthenozoospermia is often unclear and may be secondary to direct or indirect effects on sperm motility. Here, we report a case - with a brief clinical review - of recovering sperm motility after diagnosis of complete asthenozoospermia coinciding with resolution of chronic respiratory infections. The patient is a 36-year-old male, with initial semen analysis demonstrating 100% immotile sperm. Following the resolution of chronic respiratory infection, subsequent analysis demonstrated functional improvement with 76 million sperm/mL, 8% progressive motility and 4% strict morphology. Our case reinforces a potentially underappreciated role of environmental risk factors in infertility, with a focus on the patient's history of infections and other risk factors for acquired ciliary dyskinesia, which should be kept in mind when treating patients with asthenozoospermia.